Frequency of Abdominal Obesity and Its Relationship with Blood Factors and Blood Pressure Indices in Candidates for Elective Angiography Referring to Heshmat Hospital in Rasht in 2016 - M Mahdavi Roshan; A Salari; M Shakiba; M Naghshbandi; M Gholipour (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2018)
BACKGROUND AND OBJECTIVE: Considering the relationship between abdominal (central) obesity and chronic diseases and disorders of biochemical factors, as well as the role of ethnicity and geographical area on the relationship between obesity and chronic diseases, this study aims to determine the prevalence of abdominal obesity and its relationship with biochemical and blood pressure indices in candidates for angiography. METHODS: This cross-sectional study was performed on 610 subjects aged 25-75 years who were candidates for elective angiography and were referred to Heshmat Hospital in Guilan province in 2016. Data were collected by interview, medical records, blood pressure measurements and anthropometric indicators, including weight, height, body mass index and waist circumference. Fasting blood samples were used for biochemical indices. Abdominal obesity was determined based on waist circumference more than 102 cm in men and more than 88 cm in women. FINDINGS: In this study, 348 (57%) patients had abdominal obesity. 29% of men (101 patients) and 71% of women (248 patients) had abdominal obesity and there was a significant relationship between gender and abdominal obesity (p=0.0001). There was a significant different between patients with abdominal obesity and non-obese subjects in terms of total cholesterol (161±40 vs. 153±41 mg/dl, p=0.04), HDL cholesterol (44±8.6 vs. 43±8.2 mg/dl, p=0.01) and hematocrit (39±4.1 vs. 41±4.4 mg/dl, p=0.001). The variables of age, gender, and BMI were independent predictors of abdominal obesity. The incidence of abdominal obesity was 37 times higher in women and increased significantly with age. The chance of obesity increased by 1.25 per unit body mass index increase. CONCLUSION: The results of this study demonstrate the prevalence of abdominal obesity in candidates for elective angiography and its association with some blood factors.